Acoustic sniper localization - Danicki, E. (Archives of Acoustics, 2005)
Acoustic signals of small arm's fire, the muzzle blast and the shock wave generated by a supersonic bullet in air, are difficult to mask and can be exploited for localization of the hidden sniper. This paper presents the system of acoustic measurements, based on a number of both directional and omnidirectional microphones detecting the shock wave only, yielding exact solution for the sniper direction in spite of certain errors in the directional measurements. The system has a self-correcting ability concerning the sound directional measurements which contributes to the system technical feasibility. Auxiliary muzzle blast measurements would yield the sniper position. Key words: shock waves, measurements.